Numerical study on indoor temperature in multi-storey buildings - M. Srinivasa Reddy, Anjanna Matta (International Journal of Control and Automation, 2020)
The present study analyzes the thermal distribution inside the multi-storey buildings. This numerical study’s importance is to enhance the energy optimization by providing a forecasting information on the heat flow demand. A generalized mathematical modeling is used to find the performance of thermal distribution. The available information from different sources are used. The given model initiates to an optimal number of predefined variables are applied. It can be assist required optimal heat source/sink in multi-storey buildings.